Regulation of NLRP3 Inflammasome by Phosphorylation - Song, Nan; Li, Tao (Frontiers in Immunology, 2018)
The cytosolic pattern recognition receptor (PRR) NOD-like receptor family, pyrin domain containing 3 (NLRP3) senses a wide range of pathogen-associated molecular patterns (PAMPs) and damage-associated molecular patterns (DAMPs). Upon activation, NLRP3 triggers the assembly of inflammasome via the self-oligomerization and the recruitment of apoptosis-associated speck-like protein containing a caspase-recruitment domain (ASC) and pro-caspase-1, facilitating the robust immune responses including the secretion of proinflammatory cytokines and pyroptosis. The NLRP3 inflammasome must be well orchestrated to prevent the aberrant activations under physiological and pathological conditions, because uncontrolled activation of NLRP3 inflammasome is one of the major causes of a variety of autoimmune diseases and metabolic disorders. Therefore, understanding the molecular mechanisms for controlling NLRP3 inflammasome activation may provide novel strategies for the treatment of NLRP3-related diseases. Although NLRP3 inflammasome can be regulated at the transcriptional level, the post-translational modification (PTM) of NLRP3 as well as other inflammasome components has also been showed to be critical for the regulation of its activation. Several kinases and phosphatases have been shown to control NLRP3 inflammasome activation in response to either exogenous pathogen infections or endogenous molecules, such as bile acids. In this review, we summarize our current knowledge of phosphorylation patterns and their functional role in the regulation of NLRP3 inflammasome, and suggest interesting areas for future research.